Factors affecting union effectiveness: a case in Tenaga Nasional Berhad / Nur Shameela Noor Ramli - Noor Ramli, Nur Shameela (Faculty of Business and Management, 2014)
Union effectiveness is defined as the activities and organizational attributes which allow the union to achieve its goals. The purpose of this study is to determine the relationship between IV (delivery processes, improve in wages and benefits, leadership stability, union political) and DV (union effectiveness). This study was conducted at Tenaga Nasional Berhad (TNB) Negeri Sembilan and aims to address the most significant factor towards union effectiveness. 104 questionnaires were gathered in this research. The questionnaires were used to obtain and collected the data from the respondent. Simple random samplings are being used in this study as sampling design. Overall results revealed that delivery process was the most important predictor of union effectiveness. The findings obtained in this study particularly useful for both organization and union itself in understanding the importance of delivery process towards the union effectiveness. It is suggested that Union should organize itself in terms of improving communication with union members and understanding the employer business because these factors will enhance the union member’s perception of union effectiveness.